An 8-year-old girl with secondary histiocytic sarcoma with BRAFV600 mutation following T-cell acute lymphoblastic leukemia demonstrating stable disease for 3 years on dabrafenib and trametinib – a case report and literature review - Tan, Sue Lyn; Betty Ho, Lee Sue; Yew, Ting Ting; Dahziela, Yunus (BioMed Central Ltd., 2025)
Abstract Background Histiocytic sarcoma as a secondary malignancy following childhood leukemia is extremely uncommon with fewer than 20 cases reported worldwide. They often pose a diagnostic challenge and prognosis is dismal. There is a lack of well-established clinical treatment protocols owing to rarity of disease. Majority were managed with chemotherapy with variable outcomes. Case presentation Herein we report a rare case of an 8-year-old girl with secondary BRAFV600-mutant histiocytic sarcoma following T-cell acute lymphoblastic leukemia. After poor disease control with salvage chemotherapy, she was treated with MAPK-targeted therapy with dabrafenib and trametinib. She demonstrated excellent response and remained in partial remission with no signs of disease progression 3 years later. Conclusions There is yet to be consensus on the optimal management for this neoplasm. Description of our successful clinical experience highlights that investigation for BRAF mutations in histiocytic sarcoma is potentially advantageous. It also adds to the growing evidence that precision medicine may be a promising avenue to target this aggressive tumor and lays the foundation for future research. Keywords Histiocytic sarcoma, BRAF mutation, MAPK-targeted therapy